Visual and Auditory Features of Memrise in Increasing the Motivation to Learn English Vocabulary for Class X Students of SMK Negeri 3 Metro - Citra Putri Aditia; Fenny Thresia; Devi Yandika Putri; Syalum Aini (Universitas Negeri Semarang, 2025)
Although digital technology has been widely adopted in English language instruction, existing research often emphasizes general applications or large-scale platforms without closely examining how specific digital tools function within the context of vocational education. Most prior studies have focused on university students or general high school populations, with limited attention to how audio and visual elements in applications like Memrise influence motivation and vocabulary acquisition among vocational students. Furthermore, while Memrise has been recognized for its gamification and multimedia features, few empirical studies explore how these features interact with the unique learning needs, habits, and infrastructural challenges faced by students in vocational schools, particularly in rural or under-resourced settings. The lack of in-depth, context-specific studies examining the practical integration of Memrise into structured classroom routines—especially using qualitative insights—creates a significant gap in the literature. This study addresses that gap by exploring the perceptions and experiences of Class X students at SMKN 3 Metro, focusing on how Memrise’s visual, audio, and gamified elements affect motivation and vocabulary learning within a vocational education framework.